Felid scavenging in forensic taphonomic research: an experimental approach - Errickson, David; Lawrence, L.; Indra, L.; Thompson, Tim J. U. (Elsevier, 2024)
Animal scavenging on human remains presents a major challenge at a forensic scene. These lasting changes can influence the interpretation of a post-mortem interval, the overall state of the remains and any associated evidence, impacting the integrity of the scene. Therefore, identifying taphonomic related changes due to animal scavenging is important to understand the post-deposition sequence of events. However, knowing where to look is challenging and animal scavenging studies are difficult to create. Therefore, this study worked in collaboration with zoological institutes in the UK to capture the scavenging changes to horse bone, focussing on the locations of scavenging on bone and the characteristics left. This study focused on large felid (cheetah, lion, tiger, leopard) scavenging, which is less documented in comparison to canine scavenging. This research demonstrated the distribution patterns of tooth activity associated with large felid scavenging is consistent with those reported in the taphonomic literature on lions. Specifically, pits, punctures, scalloping and furrowing were found and characteristics were frequently noted at the borders and flat regions of bones. This study adds to the forensic discussion of scavenging. While focussing on large cats, the work demonstrates anatomical regions that may be affected by scavenging and the visual cues that may help identify animal interaction over human.
Keywords: 37 Earth Sciences; 31 Biological Sciences; 3702 Climate Change Science; Legal & Forensic Medicine